AN ANALYSIS OF MOTIVATION WORDS IN â€œZIG ZIGLARâ€ FANS PAGE ON FACEBOOK - Azhari, Muhammad (JURNAL LITERARY CRITICISM, 2016)
Semantic is a branch of linguistics. This branch is the important one, and there are lexical meaning and contextual meaning. By reading the motivation words, we can get knowledge about motivation and it can motivate us to be a better person. Therefore, the researcher was interested in analyzing the kinds of meaning used in motivation words in Zig Ziglar fans page.The problem of this study are : (1) what is the lexical meanings of Zig Ziglar motivation words? (2) What is the contextual meaning of Zig Ziglar?s motivation words in his fans page? (3) How is the response of the fans toward the motivation words? The researcher took twenty five motivation words to analyze. This study used a descriptive qualitative method to analyze and interpret the research object of motivation words in Zig Ziglar fans page. The step to obtain the data was by collecting sources of the data from Zig Ziglar fans page on facebook. After that, the researcher selected twenty five motivation words that contain lexical and contextual meaning, analyzed the collected data, and made conclusion. The result of this research are as follows: (1) related to the lexical meaning, while (2) related to the contextual meaning, and (3) related to the response of fans. The researcher expects this research will be useful for the other researchers who are eager to know more about semantics. Key word: Semantic, motivation words, lexical meaning,contextual meaning, ZigZiglar.